Investor reactions to corporate scandals of foreign listings. - Thia, Jian Wei. (2011)
Investors’ decision-making process has always been of interest to many researchers spanning across psychology and finance. Drawing from cognitive processing and structural management theories, this study examines the spillover effect on firms categorized as foreign-listed firms. Specifically, we examine market reactions to SGX announcements of corporate scandals on S-shares, which are firms listed in the Singapore Stock Exchange with main operations in China. Financial event study methodology revealed the existence of negative spillover effects to other S-shares not involved in the alleged scandal. The results further affirm the importance of internal and external risk indicators in investment decision-making. Overall, this study suggests that investors may be adopting a two-stage decision-making process, which first uses general categorizations to narrow down on a group of firms that may be of interest before applying specific investment criteria to make their final decisions.